Understanding Place Histories to Inform Positive Ageing-in-Place Transitions: An Intersectional Place Perspective of Forced Relocation Experiences - Fang, Mei Lan; Sixsmith, Judith; Woolrych, Ryan (International Journal of Educational and Life Transitions, 2023)
Background: Forced relocation is not always experienced as a single occurrence or event in time. Currently, there is a limited knowledge on how several substantial relocations across a lifetime impacts the health and wellbeing of older people.Aim: This study explores forced relocation experiences of older, low-income migrant Canadians through inquiries into their past place histories and examines how these have shaped opportunities and oppressions leading up to transitions into affordable housing in Richmond, BC, Canada.Methods: Informed by an intersectional place perspective model developed specifically for this research, a multi-method, qualitative community-based approach was undertaken involving in-depth interviews (N = 15), storytelling sessions (N = 10), and photo-tours (N = 8), with 28 participants. Narrative and visual data were co-analysed with participants, using a framework thematic analysis approach.Results: The analysis revealed oppressive structures that influenced the everyday lives of older people, which generated feelings of distress, fear, exclusion, feeling unsettled, and being ‘othered’. However, within oppressive structures of enforcement emerged experiences of empowerment engendered through gaining a sense of community, realising social belonging and family, maintaining pride and personal integrity as well as capturing community, social, psychological, physical and health transitions.Discussion: Unique insights acquired from an intersectional place analysis highlight how past experiences of place shape current perceptions of home and provide important implications for supporting and maintaining the health and wellbeing of older people during this type of relocation. The theoretical resource developed for this study, offers researchers, planners and developers an important tool for procuring a more critical perspective when creating homes for marginalised persons.
Keywords: Ageing-in-place; forced relocation; intersectionality; older adults; migration; place history; transitions